Sexual Harassment Criminal Law Policy In Criminal Law Revision Of Indonesian - Munawwarah Munawwarah; Eko Soponyono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Sexual harassment is behavior that approaches related to unwanted sex, including the demand for sex, and other behaviors being verbally or physically refer to sex. In studies using the theory of criminal law policy, legal certainty and legal policy research law enforcement. The result of goal against sexual offenders stipulated in the Penal Code and the Child Protection Act and women and Pornography Law issued regulations while for the area of Semarang District, is regulated by Regional Semarang District Number 1 of 2015 About the Empowerment and Protection of Women. In addition to the regulation, Semarang District Government also set about the task area devices pertaining to the protection of women and children namely Semarang Regent Regulation Number 52 Of 2016 on Positions, Organizational Structure, Duties and Functions, Work Procedures, and details of the regional Task Semarang regency. The weakness of criminal law policy against sexual harassment at this time that the recognition of the victim and the offender only from one specific sex which affects the exclusion of rape victims of the other sex, and the absence of an exact definition of sexual abuse, rape or sexual abuse, so that the diversity of cases of sexual violence understood as rape. In any law enforcement agencies have set up special treatment for sexual violence against women, whereas there is nothing available in the case of victims of sexual violence for men, this can lead to many sexual deviations that occur. Criminal law policy against sexual harassment in the reform of criminal law in Indonesia through the Bill the Code of Penal (Criminal Code draft) 2019, In these terms, rape is not just intercourse with a woman outside of marriage against the will of the woman, but rather expanded, including male insert his penis into the anus or mouth of a woman. Description of rape also in view of not just as sexual but also as a life-threatening crime, and in the abovementioned article does not describe the victim or the perpetrator of a particular gender.Key words: Policies; Criminal Law; Sexual Harassment.